ASSESSMENT OF IMPAIRMENTS OF MEMORY SEMANTIC ASPECTS IN ALZHEIMER DESEASE - Peraita, Herminia; Sánchez Bernardos, María Luisa (Anales de Psicología / Annals of Psychology, 2008)
In this work, which is part of a broader project on assessment of the deterioration of semantic memory in patients with Alzheimer-type dementia, the lexical-semantic and categorical-semantic alterations in a group of patients with probable dementia Alzheimer type, divided into two subgroups according to the degree of severity of their dementia (slight, n = 23, and moderate, n = 21) were analyzed and compared with a healthy control group (n = 30), equaled in age and sex, although it was not possible with regard to educational level. The cognitive tasks, whose results are presented in this study, that were used to analyze the aforementioned deterioration are all production tasks: fluidity of category exemplars, category definition, drawing denomination, and attribute production. In the analysis of variance carried out ( General Lineal Model of the SPSS, 7,1), the following were considered the independent variables: the kind of subject, with three levels (healthy, slightly ill, and moderately ill); the kind of item or stimulus, with two levels (belonging to animated or inanimate categories); and the kind of attribute or conceptual relations implied in the 2nd and 4th tasks. Age and educational level were considered covariants, so as to control their effect. The results reveal that age was highly significant in the categorical-fluidity and the drawing-denomination tasks, but not in the other two; the kind of group/stage of disease was highly significant in all the tasks, whereas the animate/inanimate quality of the stimuli was only significant in the attribute-denomination and production tasks. Lastly, the kind of attribute and/or the conceptual relations were again highly significant, as was the interaction between the latter and the disease stage.